Equilibrium unemployment with outsourcing and wage solidarity under labour market imperfections - Erkki Koskela; Rune Stenbacka (Center for Economic Studies and ifo Institute (CESifo), 2007)
We evaluate the effects of outsourcing and wage solidarity on wage formation and equilibrium unemployment in a heterogeneous labour market, where wages are determined by a monopoly labour union. We find that outsourcing promotes the wage dispersion between the high-skilled and low-skilled workers. When the labour union adopts a solidaristic wage policy, it will magnify, and not dampen, this tendency. Further, higher outsourcing will increase equilibrium unemployment among the high-skilled workers, whereas it will reduce it among the low-skilled workers. Overall, outsourcing will reduce economy-wide equilibrium unemployment under the reasonable condition that the proportion of high-skilled workers is sufficiently low.
Keywords: E23; E24; J31; J51; 330; Arbeitslosigkeit; Outsourcing; Lohnverhandlungen; Unvollkommener Markt; Arbeitsmarkttheorie; Theorie